PENINGKATAN KOMPETENSI GURU TATA KECANTIKAN MELALUI PELATIHAN DAN PENYEDIAAN SARANA PRAKTIK BARBER BERBASIS DUNIA INDUSTRI - Wisri Ardhita Manda Putri; Putri Chairina Zulfiani; Mei Alsih Sihombing; Irmiah Nurul Rangkuti; Asrah Rezki Fauzani; Astrid Sitompul (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
This community service activity aims to improve the competence of beautician teachers at Imelda Medan Tourism Private Vocational School through training and mentoring Barber skills based on the industrial world. The target partners are teachers who still have limitations in mastering male hair trimming techniques, do not have access to industry-based training, and lack practical facilities according to industry standards. The main problems identified include: (1) low teacher competence in barber techniques, (2) limited facilities and infrastructure to support learning, (3) unavailability of relevant industry-based training, and (4) no partnership with professional barbershop practitioners. The solutions offered include intensive training in basic to advanced techniques in men's hair trimming, provision of practical tools such as hair clipper, trimmer, and cutting scissors, and development of video tutorials as self-learning media. In addition, this activity also facilitates cooperation between schools and the World of Business and Industry (DUDI), as well as assistance in utilizing the learning media. The implementation method consists of the preparation stage, training, practical assistance, competency evaluation, and publication of activity results. The implication of this program is the establishment of an industry-based vocational training model that can be replicated in similar schools, improving the teaching quality of vocational teachers, and strengthening the synergy between vocational education institutions and industry in developing human resources that are relevant to the needs of the labor market.